Adsorption of Polyadenylic acid on graphene oxide: experiments and computer modeling. Issue 1 (2nd January 2022) - Karachevtsev, Maksym V.; Stepanian, Stepan G.; Valeev, Vladimir A.; Lytvyn, Oksana S.; Adamowicz, Ludwik; Karachevtsev, Victor A.
Abstract: In this work, we study the adsorption of poly(rA) on graphene oxide (GO) using AFM and UV absorption spectroscopies. A transformation of the homopolynucleotide structure on the GO surface is observed. It is found that an energetically favorable conformation of poly(rA) on GO is achieved after a considerable amount of time (days). It is revealed that GO can induce formation of self-structures of single-stranded poly(rA) including a duplex at pH 7. The phenomenon is analyzed by polymer melting measurements and observed by AFM. Details of the noncovalent interaction of poly(rA) with graphene are also investigated using molecular dynamics simulations. The adsorption of (rA)10 oligonucleotide on graphene is compared with the graphene adsorption of (rC)10 . DFT calculations are used to determine equilibrium structures and the corresponding interaction energies of the adenine-GO complexes with different numbers of the oxygen-containing groups. The IR intensities and vibrational frequencies of free and adsorbed adenines on the GO surface are calculated. The obtained spectral transformations are caused by the interaction of adenine with GO. Graphical Abstract: UF0001